JOINIG OF MG ALLOY AZ31B BY SELECTED TECHNOLOGIES - Tomáš Kramár; Petr Vondrouš; Miroslav Jáňa; Tomáš Kupec (Acta Polytechnica, 2019)
This contribution presents metallurgical joining of Mg alloy AZ 31B by several technologies - Friction Stir Welding - FSW, Laser Beam Welding - LBW, soldering and their mutual comparison. The difficulty of joining Mg alloys is connected with the strong MgO layer, low ductility of the weld metal (WM), a presence of intermetallic phases connected with the hardness increase. To successfully join Mg alloys, a precise setting of welding parameters is needed. The welds are susceptible to low mechanical properties as all samples fractured at WM. From the tested methods, laser beam welding proved the best results, because laser welding is the fastest and weld strength reached the highest values, i.e. 87% of BM (base metal) strength.